Sistem Pakar Untuk Mendiagnosa Gangguan Skizofrenia Menggunakan Metode Dempster Shafer - Cahyani, Cendi Nur; Yulianti, Liza; Lianda, Deri (Jurnal Media Infotama, 2024)
The development of Science and Information Technology is currently increasingly rapid, making it easier for all elements of society to use data and information quickly and accurately, one of which is using expert systems. This study aims to create an expert system for diagnosing schizophrenia, because schizophrenia is one of the mental disorders with the most patients at the Soeprapto Bengkulu special mental hospital. This expert system uses the Dempster Shafer method, a mathematical theory based on functions or belief values that is used to combine and calculate the probability of a phenomenon. This application can be accessed by patients through the registration room so that staff and patients can quickly carry out consultations without waiting for a doctor and it is hoped that it can be used by patients in early diagnosis to prevent more serious diseases. This system is designed using the PHP programming language and MySQL database,therefore the resulting expert system is able to help patients diagnose schizophrenia as well as provide fast and precise solutions to the disease they are experiencing.